2021
DOI: 10.21776/ub.jam.2021.019.02.16
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Workloads on Turnover Intention With Work Stress as Mediation and Social Support as Moderated Variables

Abstract: The purpose of this study was to examine and analyze the relationship of workload, work stress, and social support for employee turnover intentions of PT. Bentoel Prima Malang. This study uses a population of all Primary Manufacturing Department (PMD) permanent employees of 83 employees. All members of the population are used as research samples (total sampling). Analysis tool to test the relationship between variables using the help of smartPLS 3.0. The results showed that workload did not significantly influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
4
0
3
Order By: Relevance
“…It is also a delayed response to factors causing chronic interpersonal stress plus mobility in the field of occupations which are likely to be seen in relieving and counseling occupations, responsibilities, and duties of these types of jobs. Job burnout is, actually, one of the foremost reverberations of work stress [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is also a delayed response to factors causing chronic interpersonal stress plus mobility in the field of occupations which are likely to be seen in relieving and counseling occupations, responsibilities, and duties of these types of jobs. Job burnout is, actually, one of the foremost reverberations of work stress [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chung (2017) says that high work stress is linked to low job satisfaction, which means that people are more likely to want to leave their jobs. Wibowo et al (2021) showed that work stress moderates the relationship between workload and intention to leave.…”
Section: H3: Job Insecurity Has a Significant Effect On Work Stressmentioning
confidence: 99%
“…This means that the more work employees are given, the more burdened they will feel, and if the workload is too much for them, work stress will happen, leading to employee intention to leave. However, the findings of Abbas et al, 2015;Rizky et al,2021;Wibowo et al, 2021. Based on the above studies, there is a gap in the research or a difference in the results of these studies. These inconsistencies in research findings allow researchers to conduct additional research on the effects of job insecurity and workload on employee turnover intention, directly and indirectly, via mediating variables.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Sementara itu Work Stress juga dapat dipengaruhi oleh ketidakpuasan karyawan karena mereka merasa memiliki pekerjaan diluar kemampuan yang dimiliki. (Wibowo et al, 2021). Work Stress erat kaitannya dengan tuntutan kerja yang berlebihan sehingga mampu mempengaruhi niat karyawan untuk berpindah (Arshadi & Damiri, 2013).…”
unclassified